Educating elite coaches in sport—subjective experiences from a national coach education program - Østerås, M. G. O.; Fikse, C.; Riise Midtun, I.; Moen, F. (International Sport Coaching Journal, 2026)
The current study concerned elite sport coaches` experiences from participating in a nonformal coach education program, inspired by learner centeredness (LC), including mentors, and facilitated group gatherings. A reflexive thematic analysis showed three main themes: (a) the importance of a mentor-coach alliance based on trust, (b) the importance of sharing experiences and actively listening, and (c) confidence through confirmed strategies. These three themes were discussed in terms of the LC paradigm and teaching, mentoring literature, and Kolb`s learning cycle, as well as professional coaching, and self-efficacy. Concluding with a coach preference for a LC approach and the relevance of experiential learning theory and professional coaching for continued improvement in coach education and mentoring.